2022
DOI: 10.3389/fnut.2021.809783
|View full text |Cite
|
Sign up to set email alerts
|

Biofortified Wheat Increases Dietary Zinc Intake: A Randomised Controlled Efficacy Study of Zincol-2016 in Rural Pakistan

Abstract: A new variety of zinc biofortified wheat (Zincol-2016) was released in Pakistan in 2016. The primary aim of this study was to examine the effects of consuming Zincol-2016 wheat flour on biochemical and functional markers of zinc status in a population with widespread zinc deficiency. An individually-randomised, double-blind, placebo-controlled cross over design was used. Fifty households were recruited to participate in the study, with each household included at least one woman of reproductive age (16–49 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
3
14
1
Order By: Relevance
“…It reveals that pregnant and breastfeeding women in the households showed their interest to pay more for their better health after they received nutrition information. This finding is further supported by the findings of [63] who report that zinc uptake among women has increased by a range of 3-6 mg in Pakistan by using Zincol-16. The results also indicate that income has a positive impact on zinc wheat implying that increased income would improve purchasing power and hence their WTP for nutritional food like biofortified wheat along with their urge to improve family and personal health.…”
Section: Determining Factors Of Willingness To Paysupporting
confidence: 75%
“…It reveals that pregnant and breastfeeding women in the households showed their interest to pay more for their better health after they received nutrition information. This finding is further supported by the findings of [63] who report that zinc uptake among women has increased by a range of 3-6 mg in Pakistan by using Zincol-16. The results also indicate that income has a positive impact on zinc wheat implying that increased income would improve purchasing power and hence their WTP for nutritional food like biofortified wheat along with their urge to improve family and personal health.…”
Section: Determining Factors Of Willingness To Paysupporting
confidence: 75%
“…Analogous findings were provided when the efficacy of Zn biofortified wheat in improving Zn status of consumers was assessed by an individually randomized, double-blind, placebo-controlled cross over study conducted in fifty Pakistani households ( 136 ). Although a significant increase in PZC levels were seen after 4 weeks, no changes in PZC and desaturase activity levels were present after 8 weeks of dietary intervention.…”
Section: Human Studies–uncontrolled Nutrient (Dietary) Intervention A...mentioning
confidence: 89%
“…Although a significant increase in PZC levels were seen after 4 weeks, no changes in PZC and desaturase activity levels were present after 8 weeks of dietary intervention. Low dietary Zn intake contributes to reduced FADS activity, but no statistically significant associations were achieved ( 136 ).…”
Section: Human Studies–uncontrolled Nutrient (Dietary) Intervention A...mentioning
confidence: 99%
“…Given that participants and researchers on the BiZiFED2 RCT were blind to the allocation arm, the participants invited to the FGDs could have been members of households allocated to either the BiZiFED2 RCT intervention arm (n = 250, provided with flour milled from the biofortified strain of wheat (Zincol-2016)), or the control arm BiZiFED2 RCT (n = 250, given flour milled from a standard variety of wheat (Galaxy-2013). An earlier randomised controlled efficacy study conducted by the same research group reported that Zincol-2016 wheat, grown under optimal conditions of zinc fertiliser application specifically for this study, was able to achieve a mean zinc concentration of 49.3 mg/kg compared to 22.2 mg/kg in Galaxy-2013 grain [21]. Further information about the study flour (biofortified and control) and its production and distribution has been described in the BiZiFED2 study protocol [8].…”
Section: Sampling and Selection Of Study Participantsmentioning
confidence: 89%